Thermal cycling experiments for glass moulds surface texture lifetime prediction - Evaluation with the help of statistical techniques - Akdogan, A. N.; Durakbasa, M. N. (ELSEVIER SCI LTD, 2008)
In this study, test specimens consisting of stainless steel that is widely used in manufacturing glass household goods, another stainless steel specimen and the specimen of the latter material that was surface boronized are subjected to glass forming temperature in laboratory conditions, and the changing surface roughness parameters have been monitored with precise measurement techniques. The information obtained from surface texture was not only useful for determining mould surface performance but could also be used as a distinguishing mark about the quality of glassware. The results are informative about the effects of surface texture alterations during thermal cycling operations to the mould's lifetime. The data that were obtained have been evaluated by using SPSS 13.0 (Statistical Package for Social Science) and a first-order mathematical model that gives R-a (arithmetical average roughness) parameter value against cycling number, and last but not the least some material specifications have been established. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: glass mould; surface texture; precision metrology; thermal cycling; statistical analysis and evaluation; Engineering; Instruments & Instrumentation